2017
DOI: 10.1038/nrcardio.2017.23
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoplasmic reticulum–mitochondria communication in cardiovascular pathophysiology

Abstract: Repetitive, calcium-mediated contractile activity renders cardiomyocytes critically dependent on a sustained energy supply and adequate calcium buffering, both of which are provided by mitochondria. Moreover, in vascular smooth muscle cells, mitochondrial metabolism modulates cell growth and proliferation, whereas cytosolic calcium levels regulate the arterial vascular tone. Physical and functional communication between mitochondria and sarco/endoplasmic reticulum and balanced mitochondrial dynamics seem to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
104
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(104 citation statements)
references
References 221 publications
0
104
0
Order By: Relevance
“…In our study, LVEDP of the AS group tended to return to normal levels compared with the I/R group, which implied that AS could improve left ventricular diastolic function and increase myocardial positive inotropic effect [15,20]. In myocardial ischemia, mitochondrial oxidative phosphorylation and ATP production rapidly decreased, when Ca 2+ concentration in the mitochondrial matrix increased [29,30]. When the heart restored blood oxygen supply, a sufficient number of ROS generated, leading to cell membrane damage and permeability increase [29,31].…”
Section: Discussionmentioning
confidence: 94%
“…In our study, LVEDP of the AS group tended to return to normal levels compared with the I/R group, which implied that AS could improve left ventricular diastolic function and increase myocardial positive inotropic effect [15,20]. In myocardial ischemia, mitochondrial oxidative phosphorylation and ATP production rapidly decreased, when Ca 2+ concentration in the mitochondrial matrix increased [29,30]. When the heart restored blood oxygen supply, a sufficient number of ROS generated, leading to cell membrane damage and permeability increase [29,31].…”
Section: Discussionmentioning
confidence: 94%
“…The consequences of mitochondrial deformation for structural cross‐talk with the SR are not known. Previously, cytoarchitectural perturbations have been shown to affect SR‐mitochondrial functional coupling (Wilding et al, ; Joubert et al, ; Lopez‐Crisosto et al, ). Additionally, we describe electron dense RyR‐like structures between T‐tubules and mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…The close proximity of the two compartments is thought to play a role in Ca 2+ signaling, exchange, and buffering and, consequently, to modulate excitation‐contraction coupling (Duchen et al, ; Rizzuto et al, ; Lu et al, ). SR‐mitochondrial Ca 2+ transfer is believed to occur through direct physical contact in cardiomyocytes (Lopez‐Crisosto et al, ), and the molecular identity of those tethers has been previously suggested as mitofusin (Naon et al, ). Some of the structures described here share structural similarity to mitochondrial ryanodine receptors, as proposed in earlier studies (Csordás et al, ; Franzini‐Armstrong, ; Lukyanenko et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, alterations in these processes can lead to increase in cytosolic Ca 2+ with potential activation of detrimental pathways that have been associated with HF, including CaMKII (Zhang and Brown 2004). Additionally, alterations in SR-mitochondria contacts have been found in cardiac dysfunction and HF (Lopez-Crisosto et al 2017). …”
Section: Role Of Mitochondrial Ca2+ In Metabolism-contraction Coupmentioning
confidence: 99%